Temporal variability in macroinvertebrates diversity patterns and their relation with environmental factors - MOHAMMAD HASAN GERAMI; RAHMAN PATIMAR; HOSSEIN NEGARESTAN; HOJJATOLLAH JAFARIAN; MOHAMMAD SEDDIQ MORTAZAVI (Biodiversitas Journal of Biological Diversity, 2016)
Gerami MH, Patimar R, Negarestan H, Jafarian H, Mortazavi MS. 2015. Temporal variability in macroinvertebrates diversity patterns and their relation with environmental factors. Biodiversitas 17: 36-43. Seasonal changes are the most important factor in temporal variability of macroinvertebrates communities in marine benthic zone. Realizing the pattern of these changes are the key attributes to maintain benthic resources. For this purpose this study aimed to investigate temporal variability of macroinvertebrates diversity patterns in different seasons in Hormozgan province waters, Persian Gulf. Five sites were identified and sampling was carried out randomly at three places with three replicate in each site from autumn 2014 to spring 2015. Physiochemical properties of water were recorded in each sampling site. Total of 19 macroinvertebrate orders were identified form four seasons in all sites. Results showed that Polychaeta were dominant taxa in all seasons and maximum diversity of benthic macroinvertebrates exhibitedin winter. According to evenness index (E1), abundances of species were most balanced in spring. Analysis of weight and density revealed that the species diversity and mean weight of macroinvertebrates had maximum in winter and minimum in summer. Macroinvertebrate community structure was similar in the spring and summer and partly discriminated from remaining two seasons. SIMPER analysis confirmed these dissimilarities and revealed that Foraminifera, Gastropoda and Polychaeta have three major contributions in dissimilarities between seasons. According to BIO-ENV analysis, oxygen and chlorophyll a were the best variables (r = 0.7143) explaining changes in the abundance over time of the benthic fauna under study. On the contrary, eight orders (Amphipoda, Secernentea, Cumacea, Euphausiacea, Gastropoda, Isopoda, Anthozoa and Sagittoidea) did not show any convergence with environmental factors in this study.